Liberal Calvinism; The Remonstrants At the Synod of Dort in 1618 - Foster, Herbert Darling (Harvard theological review, 1923)
In spite of all the volumes written about the Synod of Dort, one looks in vain for a comparison between the condemned Remonstrants and Calvin, either in doctrine or in those other distinguishing features of the Calvinism that flowed from Calvin and Geneva, and formed the working program among Huguenots, Dutch, Scotch, English, and the descendants of all four in the American colonies.